Field researcher manual for peste des petits ruminants (PPR) surveys, in French and English - CGIAR Research Program on Livestock (2020)
The manuals have been distributed to field researchers to be used in 7 countries: Senegal, Mali, Burkina Faso, Kenya, Ethiopia, Tanzania and Uganda.